Effect of optimized new Shengmai powder on exercise tolerance in rats with heart failure by regulating the ubiquitin-proteasome signaling pathway - Wang, Shuai; Wang, Lin; Gu, Shaoke; Han, Yixiao; Li, Linfeng; Jia, Zhuangzhuang; Gao, Ning; Liu, Yu; Lin, Shanshan; Hou, Yazhu; Wang, Xianliang; Mao, Jingyuan (Frontiers in Cardiovascular Medicine, 2023)
Introduction Decreased exercise tolerance is a common symptom in patients with heart failure, which is closely related to protein degradation and apoptosis regulated by the ubiquitin-proteasome signaling (UPS) pathway. In this study, the effect of Chinese medicine, optimized new Shengmai powder, on exercise tolerance in rats with heart failure was investigated via the UPS pathway. Methods The heart failure model was prepared by ligating the left anterior descending branch of the coronary artery in rats, in which the sham-operated group was only threaded and not ligated. Rats (left ventricular ejection fraction ≤ 45%) were randomly divided into the following groups: model group, YHXSMS group, Benazepril group, and proteasome inhibitor Oprozomib group, and they were administered the corresponding drugs by gavage for 4 weeks. The cardiac function of rats was evaluated by performing an echocardiography examination and a hemodynamic test and the exercise tolerance was done by conducting an exhaustive swimming test. The mechanism was revealed by TUNEL detection, immunohistochemistry, immunofluorescence analysis, Western blot, and quantitative real-time PCR. Results The study showed that there was a decrease in cardiac function and exercise tolerance of rats in the model group and also destruction of cardiac and skeletal muscle fibers, a proliferation of collagen tissue, and an increment of apoptosis. Our study suggested that optimized new Shengmai powder could exert antiapoptotic effects on myocardial and skeletal muscle cells and improve myocardial contractility and exercise tolerance by inhibiting the overactivation of the UPS pathway, downregulating MAFbx, and Murf-1 overexpression, inhibiting the activation of the JNK signaling pathway, upregulating bcl-2 expression, and decreasing bax and caspase-3 levels. Conclusions The study showed that the optimized new Shengmai powder could improve cardiac function and exercise tolerance in rats with heart failure through the UPS pathway.